Pengembangan Aplikasi Pelayanan Dokumen untuk Mahasiswa - Rozi, Nanang Fakhrur; Mauludin, Mohammad; Rachman, Andy (P3M Politeknik Negeri Banjarmasin, 2022)
Document services are often found in government and education environments. Document service aims to produce a document as evidence or validation of something according to the request of the applicant. The document service process often does not run smoothly because there are obstacles such as the number of applicants, limited space, and limited service time. In the modern era like today, these problems can be solved by making a special application for document services in order to make it easier for applicants to submit files to the service unit. This study aims to design and build a document service application to assist applicants in requesting document services. The main feature in the application that was built is that applicants can submit the required files online without having to queue. In addition, the application that was built also has a unique feature, namely that document files that have been submitted are automatically forwarded to the related unit. This feature can assist service units in managing documents, because the requirements file does not need to be submitted manually. There is an additional feature in the form of a document service process tracking system so that applicants can see the development of services directly. The application was developed using the Spiral Model. There are four stages carried out in this model. The four stages are planning, risk analysis, development as well as testing, and evaluation. In the final stage, an application evaluation is carried out by applying the ISO 9126 standard. Based on the results of user assessments, the level of user satisfaction in terms of usability is 77.43%, functionality 78.95%, and efficiency 77.86%.